Compreensão inferencial de textos: desempenho de uma aluna do 8º ano do Ensino Fundamental - Santos, Maria Aparecida Lima Couto dos (2023)
This research aims to focus on cognitive factors, especially the inference skills, by monitoring the performance of an 8th grade elementary school student in text comprehension, based on reading/comprehension of different types of texts. Based on the theory of The Cognitive Psychology of Reading, texts in three degrees of difficulty, as organized in a study by Queiroz (2017), were distributed to a single 13-year-old participant. Nine texts with three different structures were used: narrative, argumentative and expository. The student’s performance in Reading comprehension from these different types of texts and the ability to answer questions involving inferential thinking were examined. Characterized as an application report of instruments based on Queiroz (2017), with an 8th grade Elementary School Student. Data analysis criteria were as follow: a) number of correct answers; b) answers given by the student to the inferential questions. It analyzes two moments of the collected data: the participant’s performance through the number of correct answers, and examines the answers given to the inferential questions. From the resulting scores and percentages, it is observed that the highest rate of correct answers was in the type of narrative text, with 72% of complete correct answers, and the highest index of correct answers on those texts were concentrated up to the “easy” level, making up a percentage of 83% of correct answers (partial and complete). Based on a study’s opinion, adapted from Almeida´s research (2020), the answers given by the student were collected, referring to the easy levels of the three types of texts: narrative, argumentative and expository. The student’s perception of her own performance was also evaluated. It is concluded that the student performs below her level of education, which converges with the result of the International Student Assessment Program (PISA) of 2018. It concludes that most students have a performance level significantly lower than expected even if they have more advanced education